Antibacterial and Anticancer Activities of a Fosmid Clone from Atlantis II Red Sea Brine Pool. - Nabil, Marina (AUC Knowledge Fountain, 2024)
Antimicrobial resistance (AMR) and cancer are among the top global human health issues requiring urgent control practices. AMR caused 5 million death cases around the world in 2019. This number is expected to reach 10 million deaths by 2050. Cancer deaths reached 10 million in 2020. Additionally, anticancer drug resistance is a common cause of death among cancer patients. Screening for novel compounds is one of the strategies recommended by the World Health Organization (WHO) to control drug resistance in microbial and cancer cells. Marine natural products (MNPs) are characterized by chemically diverse structures with various bioactivities, especially in extreme marine environments. Also, microbes inhabiting extreme marine environments have explicit unique mechanisms of adaptation to living in harsh conditions, having the potential for antibacterial, antiviral, and anticancer activities. Red Sea brine pools are poly- extreme environments characterized by various challenging conditions. Such unique environments are worthy of exploring to identify novel bioactive compounds. A fosmid library of environmental DNA from Atlantis II deep Lower Connective Layer (LCL) was constructed and functionally screened for antibacterial activity. 91-4H, a fosmid clone that has shown antibacterial activity, was further screened to identify the antibacterial spectrum and cytotoxicity. By the overlay assay, the clone showed a broad-spectrum antibacterial activity through a zone of inhibition against various Gram-negative and positive bacterial strains, including multi-drug resistant clinical isolates and a Mycobacterium strain. Additionally, antimycobacterial activity was molecularly measured. Moreover, the selective cytotoxic activity against cancer cells was measured by testing different concentrations of the whole cell lysate. Furthermore, the metagenomic DNA was sequenced to identify genes responsible for the experimentally tested antibacterial activity.